The Effect of Work Motivation and Discipline on the Work Effectiveness of Teachers at MTS and MAS Al Washliyah Binjai - Fikria Adelia Utari (Journal Informatic, Education and Management (JIEM), 2026)
This study examines how teacher motivation and discipline at MTS and MAS Al Washliyah Binjai affect their work productivity. A total of 33 participants were surveyed using quantitative methods in this study. A questionnaire with proven validity and reliability was used to collect data. Multiple linear regression analysis was used to determine the relative contribution of independent factors to the dependent variable to confirm the hypothesis. Data were analyzed using SPSS version 26.0. There was a favorable and statistically significant relationship between intrinsic motivation and work performance. This indicates that elements outside the scope of this study accounted for 37.6% of the variance in work productivity, with intrinsic drive and self-control contributing 62.4%. Therefore, this is crucial if the school is to achieve its vision and goals and follow its procedures.